2004
DOI: 10.1007/s00167-003-0382-7
|View full text |Cite
|
Sign up to set email alerts
|

A clinical case and anatomical study of the innervation supply of the vastus medialis muscle

Abstract: The innervation supply to the vastus medialis (VM) muscle, a component of quadriceps femoris (QF), is provided by a branch of the femoral nerve (FN) running along the muscle. The course of the nerve from lumbar roots to the muscle has been described by many researchers. It is known to ride along the femoral vein, artery and saphenous nerve and enter the adductor canal (Hunter's canal), and then to divide into branches that supply vastus medialis and the knee joint. Femoral mononeuropathy is uncommon, and is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…These two nerves are also far from the operation region. Ozer et al [21] reported that the innervation of VM was via two nerves originating from the posterior division of femoral nerve. The nerve innervating the VM muscle ran distally along the anteromedial border of the muscle and the saphenous nerve.…”
Section: Discussionmentioning
confidence: 98%
“…These two nerves are also far from the operation region. Ozer et al [21] reported that the innervation of VM was via two nerves originating from the posterior division of femoral nerve. The nerve innervating the VM muscle ran distally along the anteromedial border of the muscle and the saphenous nerve.…”
Section: Discussionmentioning
confidence: 98%
“…The medial vastus nerve lies deep to the sartorius muscle and superficial to the roof of the AC, outside the AC. 25,27 We have performed dissections of the AC in 4 cadavers at the Division of Clinical and Functional Anatomy, Medical University of Innsbruck, Austria, to solve this paradox. All 8 dissections showed that the medial vastus nerve lies outside the AC in a separate fascial tunnel on the medial vastus muscle (Fig.…”
Section: Blockade Of Femoral Nerve Branches Inside and Around The Acmentioning
confidence: 99%
“…1 An accessory obturator nerve branch is present in 10% to 30% of human beings. 27 It sometimes innervates the adductor muscle via a communication with the anterior branch of the obturator nerve, but it does not innervate the knee. 33 The anterior and posterior obturator nerve branches can be blocked concomitantly with an ultrasound-guided subpectineal approach between the pectineus and external obturator muscles proximal to the adductor brevis muscle (Fig.…”
Section: Obturator Nerve Blockmentioning
confidence: 99%
“…8 This form of nerve stimulation differs from the usual stimulation of an afferent motor nerve, as it is a direct stimulation of im branches of the nerve. The motor nerve supplying the vastus medialis muscle origins from the posterior divisions of the femoral nerve and is entering the vastus medialis from its deep surface, [17][18][19] in a bi-layered fascial envelope next to the Hunter's canal (adductor canal), where direct stimulation is not possible. This was pointed out in a commentary 20 in response to Saitoh's study.…”
Section: Discussionmentioning
confidence: 99%